Structural analysis of mitochondrial rRNA gene variants identified in patients with deafness - Vila-Sanjurjo, Antón; Mallo, Natalia; Elson, Joanna L.; Smith, Paul M.; Blakely, Emma L.; Taylor, Robert W. (Frontiers in Physiology, 2023)
The last few years have witnessed dramatic advances in our understanding of the structure and function of the mammalian mito-ribosome. At the same time, the first attempts to elucidate the effects of mito-ribosomal fidelity (decoding accuracy) in disease have been made. Hence, the time is right to push an important frontier in our understanding of mitochondrial genetics, that is, the elucidation of the phenotypic effects of mtDNA variants affecting the functioning of the mito-ribosome. Here, we have assessed the structural and functional role of 93 mitochondrial (mt-) rRNA variants thought to be associated with deafness, including those located at non-conserved positions. Our analysis has used the structural description of the human mito-ribosome of the highest quality currently available, together with a new understanding of the phenotypic manifestation of mito-ribosomal-associated variants. Basically, any base change capable of inducing a fidelity phenotype may be considered non-silent. Under this light, out of 92 previously reported mt-rRNA variants thought to be associated with deafness, we found that 49 were potentially non-silent. We also dismissed a large number of reportedly pathogenic mtDNA variants, 41, as polymorphisms. These results drastically update our view on the implication of the primary sequence of mt-rRNA in the etiology of deafness and mitochondrial disease in general. Our data sheds much-needed light on the question of how mt-rRNA variants located at non-conserved positions may lead to mitochondrial disease and, most notably, provide evidence of the effect of haplotype context in the manifestation of some mt-rRNA variants.